SEX CHARACTERISTICS OF THE MICROCIRCULATION IN HEALTHY SUBJECTS AND IN PATIENTS WITH THE FIRST DEGREE ARTERIAL HYPERTENSION - V. I. Podzolkov; L. V. Vasil'eva; V. V. Matveev; N. A. Kolesnichenko (Столичная издательская компания, 2015)
Aim. To study the sex characteristics of microcirculation in healthy volunteers and in patients with degree 1 arterial hypertension (HT). Material and methods. Patients (n=71; 34 men and 37 women) with degree 1 HT participated in the study. Besides 28 normotensive men and 41 women were included. The microcirculation study was performed with LAKK-02 analyzer on the palmar surface of the third finger of the right hand. The average values of the microcirculation index, the standard deviation of perfusion fluctuations (σ), the variation coefficient of tissue blood flow (Kv) were evaluated. Results. The microcirculation index in HT men 26.64 (21.00-32.45) perfusion units (p.u.) was significantly higher than this in HT women 20.91 (16.98-24.30) p.u., p=0.031. The variability of microcirculation index was significantly higher in HT patients than this in healthy subjects. Capillary blood flow reserve in healthy women was higher than this in healthy men. Amplitude, reflexing myogenic factor of blood flow regulation was significantly lower in HT men than this in HT women: 13.37 (10.51-16.43) vs 14.69 (11.35-19.13), respectively , p=0.023. Amplitudes, reflecting respiration effects on peripheral blood flow in HT men were significantly higher than these in HT women. Amplitudes, reflecting pulse effect on the tissue perfusion in HT women were significantly higher than these in HT men. Influence of sympathetic adrenergic innervation on the blood flow was higher in healthy men than this in healthy women. Conclusion. Received data suggests the intensification of microcirculation regulation mechanisms in men with HT degree 1. It was found that sympathetic adrenergic effect on the microcirculation regulation was significantly less in healthy women than this in healthy men.